In a secondary care setting, differences between neck pain subgroups classified using the Quebec task force classification system were typically small - A longitudinal study - Rasmussen, H.; Kent, Peter; Kjaer, P.; Kongsted, A. (Biomed Central Ltd, 2015)
Background: The component of the Quebec Task Force Classification System that subgroups patients based on the extent of their radiating pain and neurological signs has been demonstrated to have prognostic implications for patients with low back pain but has not been tested on patients with neck pain (NP). The main aim of this study was to examine the association between these subgroups, their baseline characteristics and outcome in chronic NP patients referred to an outpatient hospital department. Methods: This was an observational study of longitudinal data extracted from systematically collected, routine clinical data. Patients were classified into Local NP only, NP + arm pain above the elbow, NP + arm pain below the elbow, and NP with signs of nerve root involvement (NP + NRI). Outcome was pain intensity and activity limitation. Associations were tested in longitudinal linear mixed models. Results: A total of 1,852 people were classified into subgroups (64 % females, mean age 49 years). Follow ups after 3, 6 and 12 months were available for 45 %, 32 % and 40 % of those invited to participate at each time point. A small improvement in pain was observed over time in all subgroups. There was a significant interaction between subgroups and time, but effect sizes were small. The local NP subgroup improved slightly less after 3 months as compared with all other groups, but continued to have the lowest level of pain. After 6 and 12 months, those with NP + pain above the elbow had improved the least and patients with NP + NRI had experienced the largest improvements in pain intensity. Similar results were obtained for activity limitation. Conclusions: This study found baseline and outcome differences between neck pain subgroups classified using the Quebec Task Force Classification System. However, differences in outcome were typically small in size and mostly differentiated the local NP subgroup from the other subgroups. A caveat to these results is that they were obtained in a cohort of chronic neck pain patients who only displayed small improvements over time and the results may not apply to other cohorts, such as people at earlier stages of their clinical course and in other clinical settings.